Modelling the mass budget and future evolution of Tunabreen, central Spitsbergen - Adrian Luckman (The Cryosphere, 2022)
The 26 km long tidewater glacier Tunabreen is the most frequently surging glacier in Svalbard, with four documented surges in the past 100 years. We model the evolution of this glacier with a minimal glacier model (MGM), in which ice mechanics, calving, and surging are parameterized. The model geometry consists of a flow band to which three tributaries supply mass. The calving rate is set to the mean observed value for the period 2012–2019 and kept constant. For the past 120 years, a smooth equilibrium line altitude (ELA) history is reconstructed by finding the best possible match between observed and simulated glacier length. There is a modest correlation between this reconstructed ELA history and an ELA history based on meteorological observations from Longyearbyen.Runs with and without surging show that the effect of surging on the long-term glacier evolution is limited. Due to the low surface slope and associated strong height–mass-balance feedback, Tunabreen is very sensitive to changes in the ELA. For a constant future ELA equal to the reconstructed value for 2020, the glacier front will retreat by 8 km during the coming 100 years. For an increase in the ELA of 2 m a−1, the retreat is projected to be 13 km, and Tunabreen becomes a land-terminating glacier around 2100.The calving parameter is an important quantity: increasing its value by 50 % has about the same effect as a 35 m increase in the ELA, with the corresponding equilibrium glacier length being 17.5 km (as compared to 25.8 km in the reference state).Response times vary from 150 to 400 years, depending on the forcing and on the state of the glacier (tidewater or land-terminating).